Retention characteristics of lanthanum-doped bismuth titanate films annealed at different furnaces - Simões, Alexandre Zirpoli [UNESP]; Aguiar, E. C. [UNESP]; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V. Sa, 2009)
Lanthanum-doped bismuth titanate thin films (Bi(3.25)La(0.75)Ti(3)O(12) - BLT) were prepared by the polymeric precursor method and crystallized in the microwave and conventional furnaces. The obtained films are polycrystalline in nature and its ferroelectric properties were determined with remanent polarization P(r) and a coercive field E(c) of 3.9 mu C cm(-2) and 70 kVcm(-1) for the film annealed in the microwave furnace and 20 mu Ccm(-2) and 52 kVcm(-1) for the film annealed in conventional furnace, respectively. Better retention characteristics were observed in the films annealed in conventional furnace, indicating that our films can be a promise material for use in the future FeRAMS memories. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Thin films; Annealing; Atomic force microscopy; Ferroelectricity